Implementation management of corporate social responsibility in SIRCLO #BelajarBarengMentor program - Arvian, Farrel Fauzan; Budiana, Heru Ryanto (Faculty of Communication Sciences Universitas Padjadjaran, 2022)
COVID-19 pandemic in Indonesia has impacts on disabilities. The private sector can help empower them through Corporate Social Responsibility (CSR). SIRCLO is one company that initiated CSR with Difalink through the #BelajarBarengMentor Program. During the implementation, several problems were faced by SIRCLO and Difalink, even though the proper implementation of CSR can benefit the company. This study aims to determine (1) How the Plan, (2) How the Implementation, (3) How the Checking, and (4) How the Evaluation in the Implementation Management of CSR in the #BelajarBarengMentor Program with analysis using the Hohnen CSR implementation model (Plan, Do, Check, and Improve). The method used is a qualitative descriptive study with data collection through interviews, observations, and literature studies. The validity of this research uses source triangulation. The study's results revealed similarities with the Hohnen model. On (1) Planning, assessment, and strategy development were initiated, but the research needed more depth and detail. On (2) Implementation, focus on program development and execution, but there are some technical problems and exposures. On (3) Checking; it had not been conducted effectively, and on (4) Evaluation; there are several evaluations and suggestions, such as the need for solid planning and a dedicated team. The suggestions given are (1) Planning; conducting in-depth research, (2) Implementation; making alternative implementation options based on research, (3) Checking; conducting the monitoring according to the concept of CSR, and (4) Evaluation; conducting solid planning and create a dedicated team for sustainable plans.